On the Devolution of Copyright Scholarship: Part I— Tracing the Digital Copyright Revolution - Menell, Peter S. (The Columbia Journal of Law & the Arts, 2026)
As the digital revolution unfolded in the 1990s and early 2000s, a charismatic hacktivist faction took hold in the copyright legal academy. In its purest form, the copyleft movement celebrated the notion that “information wants to be free” and opposed copyright protection in cyberspace. Some copyleft scholars served as lead counsel in efforts to overturn copyright legislation and immunize filesharing enterprises from copyright liability, blurring the line between interpretive scholarship and policy analysis. Many academic amicus briefs took on the tactics of zealous advocates, selectively and misleadingly presenting empirical, statutory, and doctrinal analysis. This Article chronicles the evolution of copyright law while tracing the devolution of copyright scholarship through this tumultuous era. It highlights the origins of the copyleft movement and ways in which many scholars lost sight of essential academic values—independence, objectivity, transparency, scrupulousness, methodological soundness, and analytical rigor—in an effort to persuade courts to remake copyright law through less than forthright and non-democratic means. In the process, they eroded the trust that courts had placed in the legal academy. As the Article shows, the courts have largely remained faithful to the rule of law in copyright cases and this has for the most part promoted cultural, social, and economic progress. A follow-on article examines the chasm between judicial interpretation of copyright law and the views of many in the copyright academy through an empirical examination of Supreme Court academic briefs, anthropological analysis of the copyright legal academy. It then assesses the ramifications of the devolution of copyright scholarship for the judiciary, democratic institutions, the scholarly community, and society at large.